Knowledge, Attitude and Willingness Towards Organ Donation among People Attending Out Patient Departments of a Tertiary Care Hospital, West Bengal: A Cross-sectional Study - Bobby Syiemlieh; Obangkokla O; Mousumi Khatun; Poonam Joshi; Latha T; Jamuna R Rani; Ajay Mallick (Journal of Caring Sciences)
Introduction: Organ donation rate in India is lower compared to many developed countries. A shortage of organs for individuals in need persists, as people are hesitant to donate. The study aimed to assess knowledge, attitude and willingness toward organ donation among people attending outpatient department (OPD) of a tertiary care hospital. Methods: A descriptive cross-sectional survey design was used and 350 adults attending OPDs were recruited by convenience sampling. The participants were interviewed using structured questionnaires on knowledge, attitude and willingness towards organ donation. Data were analyzed in terms of frequency and percentage, and association was established with Fisher’s exact test. Results: The mean (SD) age of participants was 38.56 (11.18) years. The majority of participants (98.3%) had heard about organ donation through mass media. Among them, 30.3% had good knowledge and 69.1% had average knowledge. Despite having positive attitude towards organ donation, only 33.1% were willing to donate. The main reasons to donate their organs were to save the life (35.3%) and to avoid unnecessary wastage (41.3%). However, 47% were undecided to donate organs. More than half of the participants (58%) were willing to donate their blood compared to other organs. There was a significant association between the participants’ knowledge and their willingness to donate organs. A significant association was found between gender, religions, and education with willingness to donate organs. Conclusion: The participants’ willingness to donate organs was low, necessitating to organise impactful awareness programs on organ donation among general public.